Perubahan Perilaku Pada Anak Berhadapan Dengan Hukum Dalam Proses Support Group Di Sentra Handayani Jakarta - Tiara Novita; Sokhivah Sokhivah; Gwn Gwn (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Children who have legal conflicts and are victims of criminal acts must be served seriously and continuously. One of the processes of children's social reintegration is to help children develop their own thinking and abilities and think critically in everyday life. It is hoped that support group therapy will help the group restrain and improve to avoid returning to deviant behavior. Changes in Children's Behavior in Contact with the Law (ABH) in the Support Group Process at Sentra Handayani Jakarta are discussed in this research. This research method is qualitative and the nature of the research is descriptive.Changes in children's behavior occur at each group stage. This includes the child's initial adaptation (precomtemplation), awareness of the problem (comtemplation), slight changes in behavior (preperation), and starting to improve behavior (action). To maintain changes in behavior, children need rewards and punishments.